Furan-based copoly(ester-ethers) and copoly(ester-amide-ethers). Comparison study on the phase structure, mechanical and thermal properties. (13th March 2023) - Paszkiewicz, Sandra; Walkowiak, Konrad; Irska, Izabela; Zubkiewicz, Agata; Figiel, Paweł; Gorący, Krzysztof; El Fray, Mirosława
Abstract: Two series of furan-based copolymers, by means of poly(esters-ethers) (PEEs) and poly(ester-amide-ethers) (PEAEs) with various content of ether-containing blocks, have been prepared using two-stage melt polycondensation process. The molecular structure of the synthesized materials has been analyzed by Proton Nuclear Magnetic Resonance ( 1 H NMR) and Fourier Transform Infrared (FTIR) spectroscopies. In order to evaluate phase transition temperatures, as well as the thermal effects in the synthesized series of copolymers, Differential Scanning Calorimetry (DSC), Dynamic Mechanical Thermal Analysis (DMTA), and Thermogravimetric Analysis (TGA), have been performed. The synthesized copolymers exhibit a good combination of mechanical and processing properties, which resulted from high molecular masses (confirmed by Size Exclusion Chromatography (SEC) and Limited Viscosity Number (LVN)). The incorporation of both PPAF and PTMO segments into PTF affected the ability of PTF for cold crystallization, while the introduction of the amide sequences alone, influenced the overall stiffness of the system: higher values of glass transition (Tg ) and hardness. Additionally, the obtained PEEs and PEAEs do not undergo crystallization during cooling from the melt. One confirmed that the addition of PTMO had a significant effect on thermal and thermo-oxidative stability and tensile and cyclic properties. In addition, when comparing the PEE series with the PEAE series with the same PTMO content (50 wt%), it was shown that PEE 50/50 has about 3.1 and 1.25 times higher value of E compared to PEAE 50/50 at a crosshead speed rate of 5 and 100 mm/min, resulted from higher Xc (investigated by XRD analysis). Graphical abstract: Image 1 Research highlights: Furan-based sustainable copolymer were prepared by melt polycondensation. Copolymers exhibit a good combination of mechanical and processing properties. Strong effect from the incorporation of amide and ether segments was confirmed Amide segments caused chain stiffening and thus hindering the crystallization.